Camostat mesylate against SARS‐CoV‐2 and COVID‐19—Rationale, dosing and safety. Issue 2 (22nd November 2020) - Breining, Peter; Frølund, Anne Lier; Højen, Jesper Falkesgaard; Gunst, Jesper Damsgaard; Staerke, Nina B.; Saedder, Eva; Cases‐Thomas, Manuel; Little, Paul; Nielsen, Lars Peter; Søgaard, Ole S.; Kjolby, Mads
Abstract: The coronavirus responsible for COVID‐19, SARS‐CoV‐2, utilizes a viral membrane spike protein for host cell entry. For the virus to engage in host membrane fusion, SARS‐CoV‐2 utilizes the human transmembrane surface protease, TMPRSS2, to cleave and activate the spike protein. Camostat mesylate, an orally available well‐known serine protease inhibitor, is a potent inhibitor of TMPRSS2 and has been hypothesized as a potential antiviral drug against COVID‐19. In vitro human cell and animal studies have shown that camostat mesylate inhibits virus‐cell membrane fusion and hence viral replication. In mice, camostat mesylate treatment during acute infection with influenza, also dependent on TMPRSS2, leads to a reduced viral load. The decreased viral load may be associated with an improved patient outcome. Because camostat mesylate is administered as an oral drug, it may be used in outpatients as well as inpatients at all disease stages of SARS‐CoV‐2 infection if it is shown to be an effective antiviral agent. Clinical trials are currently ongoing to test whether this well‐known drug could be repurposed and utilized to combat the current pandemic. In the following, we will review current knowledge on camostat mesylate mode of action, potential benefits as an antiviral agent and ongoing clinical trials.